Self-regulation of academic emotions: recent research and prospective view - Mar´tinez-López, Zeltia; Villar, Eva; Castro, María; Tinajero, Carolina (Anales de Psicología / Annals of Psychology, 2021)
In this paper, a review of the scientific literature on the self-regulation of academic emotions is offered. A systematized search of documents was carried out in the Scopus and Web of Science databases. A total of 29 articles and book chapters were selected, which met the previously established eligibility criteria. Data and theoretical interpretations were collected that have allowed us to obtain a global vision of the state of knowledge about the principal nuclei of interest: types and frequency of use of emotional self-regulation strategies, situational conditions in which they are applied, correlates of their use and individual moderating differences.